Voice and ageing: clinical, endoscopic and acoustic investigation - Pessin, A. B.B. [UNESP]; Tavares, E. L.M. [UNESP]; Gramuglia, A. C.J. [UNESP]; de Carvalho, L. R. [UNESP]; Martins, R. H.G. [UNESP] (Wiley, 2017)
Vocal symptoms are frequent in the elderly and are consequences of structural changes in the larynx that occur with ageing. Objective: To identify the voice alterations in elderly patients attending a voice clinic. Methods: Elderly patients of both genders were divided into two groups: 60–75 and above 76 years. All patients completed a questionnaire with identification data, profession, vocal symptoms, hearing, habits and addictions, and systemic diseases. All participants were submitted to video laryngoscopy and acoustic and auditory-perceptual vocal analysis. Results: In this study, women predominated (40 F versus 32 M). Hoarseness was reported by 34.72% of the participants. Other symptoms included singing difficulty (17%) and phonatory effort (15.28%). Maximum phonation time showed lower values and scores 2 and 3 of perceptual analysis were registered in 33% of the elderly participants, but without statistical significance. The fundamental frequency values were inferior in older man and high in women and acoustic parameters showed high values in both groups, but without statistical significance. Videolaryngoscopies demonstrated alterations in 47% of the participants, especially bowed and atrophic vocal folds. Conclusions: We described the vocal symptoms, vocal perceptual and acoustic analysis and endoscopic findings of an elderly population, characterising the presbyphonia. Therapeutic measures must involve speech therapy and/or surgery to reduce the glottal gap, allowing less air leakage and, consequently, better vocal performance.